Understanding the impact of visual representation restrictiveness on experience sharing: An experimental assessment. (December 2015) - Alexander, Elitsa; Bresciani, Sabrina; Eppler, Martin J.
Abstract: This study investigates the effects of the restrictiveness of visuals on the communication process and outcome in small groups. Visual restrictiveness is conceived as the constraints imposed by a graphic template on the process of knowledge work. Through an experiment with ninety six experienced professionals we test the impact of a medium and a high level of visual restrictiveness compared to a control condition. As predicted, the results show that a medium level of visual restrictiveness, embodied in a grid layout, leads to higher experience sharing effectiveness. The impact is mediated by the structural pattern of appropriation of the interactive graphical template (assessed with content analysis). The implications of this study include extending the benefits and applications of visual representations to support group communication and the development (and testing) of the concept of visual restrictiveness. Highlights: We study the effects of visual restrictiveness on knowledge sharing effectiveness. We experiment with three levels of restrictiveness: none, medium and high. A medium level of visual restrictiveness positively impacts experience sharing. More meaningful concepts will be shared and documented at the medium level. More individual thoughts will be shared and documented at the medium level.